The Preventing Narcotics and Illegal Drug Abuse Toward Indonesia’s Golden Vision 2045 - Sri Endah Wahyuningsih; Anis Mashdurohatun (LAW FACULTY UNISSULA, 2025)
Abuse of narcotics and illegal drugs poses a serious threat to the development of Indonesia’s human resources, particularly among adolescents who represent the backbone of the nation’s future. According to data from the National Narcotics Agency (BNN, 2024), the prevalence of drug abuse in Indonesia has reached 1.73% of the productive-age population, with an increasing trend among students and university youth. This community service program aims to enhance adolescents’ awareness, knowledge, and resilience against the dangers of drug abuse through educational and participatory approaches based on school and community engagement in Banjarnegara Regency, Central Java. The implementation method adopts Participatory Action Research (PAR), consisting of stages such as socialization, peer educator training, the digital campaign “Generasi Bersinar 2045” (Shining Generation 2045), and evaluation through pre-test and post-test to measure program effectiveness. The results indicate a 49% increase in participants’ knowledge after the activities, the establishment of an anti-drug student network, and greater school participation in the “Drug-Free School” (Bersinar) movement. This program contributes to the achievement of Sustainable Development Goal (SDG) No. 3 – Good Health and Well-being, and supports human resource development toward Golden Indonesia 2045.